An Example of Turkish Stamps from Anatolia Harran Ulu Mosque - Yasin Cemal Galata (Avrasya İncelemeleri Dergisi)
The historical Harran District of Şanlıurfa is one of the rare spots that bear the traces of many civilizations throughout history due to its geographical location. The region has been a religious, economic, and cultural center since before the time of Christ and has managed to preserve the traces of different civilizations up to the present. Turkish tribes migrated from the Eurasian geography westward at different periods in history, and this has had important historical consequences. While a significant portion of these migrations spread over Europe via the Black Sea, another portion headed to the interior of Anatolia by way of the Caucasus. Harran is located at the crossroads of migration routes and practically became a center where Turkish tribes intersect. The region had been attacked by the Hun Turks prior to the Manzikert Victory and remained under the rule of many Turkish states, including the Kharezmites, Ayyubids, Mamluks, Seljuks, and Ottomans. Thus, Harran gained its place in history as a region where Turkish tribes have settled. Rock paintings, markings with Turkish motifs, and Turkish tribal engravings are the symbols of cultural unity and integrity in the geographies where the Turkish population lives, and these document the ancient traces of the Turks in the Harran region. This study discusses the traces of the Turkish tribal stamps that were found on the walls surrounding the old Grand Mosque of Harran.